Fun Fotografi on Biodiversitas: Pelatihan Fotografi sebagai Upaya Pelestarian Biodiversitas di Nagari Kasang, Kabupaten Padang Pariaman: Fun Photography on Biodiversity: Photography Training as an Effort to Preserve Biodiversity in Nagari Kasang, Padang Pariaman Regency - Pratama, Sandi Fransisco; Kardiman, Reki; Satria, Rijal; Fadilaturahmah, Fadilaturahmah; Ade, Filza Yulina; Kurniati, Rahmi; Sulaeman, Nabila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
By 2050, it is estimated that 45% of the world's species and habitats will be lost.